Pengembangan media pembelajaran pengelasan model shielded metal arc welding (SMAW) bagi siswa SMK - Bambang Sudarsono (Universitas Sarjanawiyata Tamansiswa, 2020)
This study aims to develop a suitable welding learning media that can increase the interest and learning achievement of Vocational High School (SMK) students. The research design used the Research and Development (R & D) method with the research subjects being students of SMK Ma'arif Kebumen and SMK Ma'arif Wates who were divided into control class and experimental class. Collecting data to determine the feasibility of the media using a questionnaire method (questionnaire). Meanwhile, to determine the increase in learning achievement using performance tests. Test data analysis using normality test, homogeneity test and t-test. The results showed that the SMAW Model Welding Learning Media was very feasible to use for learning media, students' interest in learning did not show differences in practical interest in the experimental class and the control class, meaning that the average practical interest in the experimental class and the control class did not have a significant difference. Student learning achievement in the experimental class was 85.25, while the results of the control class were 73.00. It can be concluded that the use of Shielded Metal Arc Welding (SMAW) learning media is feasible to be used as a welding learning medium, fosters interest in learning and can improve student achievement.